总述:本次共解1题。其中
☆算术计算1题
〖1/1算式〗
作业:求算式 5×((32-26)^2+(32-19)^2+(26-32)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2) 的值.
题型:数学计算
解:
5×((32-26)^2+(32-19)^2+(26-32)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+(32-19)^2+(26-32)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(26-32)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(-9)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(-9)^2+(-1)^2+(17-14)^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(-9)^2+(-1)^2+3^2+(14-19)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(-9)^2+(-1)^2+3^2+(-5)^2+(14-17)^2)
=5×(6^2+13^2+(-6)^2+7^2+8^2+9^2+(-13)^2+(-7)^2+5^2+(-8)^2+1^2+(-9)^2+(-1)^2+3^2+(-5)^2+(-3)^2)
=5×868
=4340 答案:5×((32-26)^2+(32-19)^2+(26-32)^2+(26-19)^2+(26-18)^2+(26-17)^2+(19-32)^2+(19-26)^2+(19-14)^2+(18-26)^2+(18-17)^2+(17-26)^2+(17-18)^2+(17-14)^2+(14-19)^2+(14-17)^2)=4340你的问题在这里没有得到解决?请到 热门难题 里面看看吧!